Renal Cell Carcinoma - Recent Advances, New Perspectives and Applications 2023
DOI: 10.5772/intechopen.107051
|View full text |Cite
|
Sign up to set email alerts
|

Clear Cell Renal Cancer, a Tumour with Neuroendocrine Features Originating from the Erythropoietin-Producing Cell

Abstract: The dominating type of kidney cancer is the clear cell renal cell cancer (ccRCC), hitherto been thought to develop from proximal tubule cells. However, the ability of tubule cells to proliferate is at best controversial. ccRCCs show many peculiarities like erythrocytosis due to erythropoietin overproduction and a combination of early metastases and sometimes apparent dormancy and late recurrence, features in common with neuroendocrine tumours (NETs). We have shown that most ccRCCs express erythropoietin and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…It is, however, well-known that a small proportion of patients with clear cell renal cell cancer (CCRCC) has erythrocytosis and a larger part EPO production in the cancer cells ( Palapattu et al, 2002 ; Wiesener et al, 2007 ). In a study applying immunohistochemistry with high sensitivity we found that practically all CCRCCs expressed erythropoietin as well as the neuroendocrine marker neuron-specific enolase (NSE) ( Mjønes et al, 2017 ), the latter a marker with hitherto misrecognized reputation.We concluded that CCRCC (the dominating histological type of kidney cancer) ( Mjønes et al, 2017 ; Waldum et al, 2022 ) originated from the EPC. There are many features in CCRCC in common with neuroendocrine tumours ( Waldum et al, 2022 ).…”
Section: Hif and Renal Cancermentioning
confidence: 91%
See 1 more Smart Citation
“…It is, however, well-known that a small proportion of patients with clear cell renal cell cancer (CCRCC) has erythrocytosis and a larger part EPO production in the cancer cells ( Palapattu et al, 2002 ; Wiesener et al, 2007 ). In a study applying immunohistochemistry with high sensitivity we found that practically all CCRCCs expressed erythropoietin as well as the neuroendocrine marker neuron-specific enolase (NSE) ( Mjønes et al, 2017 ), the latter a marker with hitherto misrecognized reputation.We concluded that CCRCC (the dominating histological type of kidney cancer) ( Mjønes et al, 2017 ; Waldum et al, 2022 ) originated from the EPC. There are many features in CCRCC in common with neuroendocrine tumours ( Waldum et al, 2022 ).…”
Section: Hif and Renal Cancermentioning
confidence: 91%
“…In a study applying immunohistochemistry with high sensitivity we found that practically all CCRCCs expressed erythropoietin as well as the neuroendocrine marker neuron-specific enolase (NSE) ( Mjønes et al, 2017 ), the latter a marker with hitherto misrecognized reputation.We concluded that CCRCC (the dominating histological type of kidney cancer) ( Mjønes et al, 2017 ; Waldum et al, 2022 ) originated from the EPC. There are many features in CCRCC in common with neuroendocrine tumours ( Waldum et al, 2022 ). HIF is a major stimulator of EPO production, whereas von-Hippel Lindau factor is central in HIF degradation.…”
Section: Hif and Renal Cancermentioning
confidence: 91%
“…In another study, NSE expression was highest among tumours of neuroendocrine origin and ccRCC 10. Thus ccRCC may be a neuroendocrine tumour too, however, the nomenclature and classification of ccRCC remain yet to be modified 11…”
Section: Descriptionmentioning
confidence: 98%
“…Moreover, more tumors develop from NE cells than presently recognized. For instance, we have shown that the most prevalent type of kidney cancer, clear cell renal cell cancer (CCRCC), most likely originates from EPO cells ( 21 , 22 , 33 ). Clinically, these tumors exhibit similarities to NETs, including early metastases, low response to cytotoxic drugs, and, parallel to hormonal overstimulation in NETs, erythrocytosis in a subset of patients.…”
Section: Cell Of Origin: Differentiated Versus Stem Cellsmentioning
confidence: 99%
“…Clinically, these tumors exhibit similarities to NETs, including early metastases, low response to cytotoxic drugs, and, parallel to hormonal overstimulation in NETs, erythrocytosis in a subset of patients. They also share positivity for neuron-specific enolase (NSE) ( 33 , 34 ). NSE is a more specific neuroendocrine marker than ordinarily believed ( 34 ).…”
Section: Cell Of Origin: Differentiated Versus Stem Cellsmentioning
confidence: 99%